AN EVALUATION OF ENGLISH LEARNING MATERIALS INFORMATION AND TECHNOLOGY STUDENTS - Astuti, Indri; Adha, Annisha Dyuli (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2022)
This research was aimed to find suitable criteria of English Materials appropriately needed by Information and Technology students. This evaluation process was used to find suitability between materials and criterion in language area, content and methodology. This research was evaluation research. Questionnaire, interview guideline, and analysis format were used to collect analysis data. The result of the data shows: (1) some of the criteria of English Materials appropriately needed in language area was already suitable with for students need. On the other hand, in writing and reading were still need improvement. (2) In language area, the suitability between materials and criteria were 58%. (3) In content, the suitability between materials and criteria were 42%. (4) In Methodology, the suitability between materials and criteria were 42%.